Reformulation of Commercial Court Authority Regulations Relation to the Arbitration Clause - Al-Anshori, Huzaimah; Handayani, Emi Puasa; Jha, Gautam Kumar (Journal of Law and Legal Reform, 2024)
The issue of jurisdiction in dispute resolution within the Commercial Court arises when the contract designates an arbitration clause as the preferred mechanism for resolving disputes. In the contractual agreement between PT. Swadaya Graha and PT. Rayon Utama Makmur (RUM), the chosen forum for dispute resolution is stipulated to be the National Arbitration Board (BANI). However, concurrently, there is a proposal for dispute resolution within the Commercial Court framework concerning defaulted debt and receivable disputes in PKPU case number 45/Pdt.Sus-PKPU/2020/PN Niaga Smg. This has engendered a legal debate centring on the application of the "lex specialist derogat legi general" principle among the Arbitration Law, the Bankruptcy Law, and PKPU, with regard to the absolute jurisdiction of institutions authorized to examine, decide, and adjudicate incidents of defaulted debt and receivable disputes within the legal relationship between the PKPU Petitioner and the Respondent. The PKPU process is structured within a contract that includes an arbitration clause as the designated dispute resolution mechanism. Given the complications and hurdles posed by these issues, there is a pressing need for legal certainty in the future. Furthermore, there has been a conflict of norms between the Arbitration Law the Bankruptcy Law and PKPU, as evidenced in PKPU case number 45/Pdt.Sus-PKPU/2020/PN Niaga Smg. Hence, a reformulation of the Bankruptcy Law and PKPU regulations is essential to harmonize them with evolving norms and address emerging issues. A vital aspect of this reformulation involves the potential removal or replacement of Article 303 of the Bankruptcy Law and PKPU.